As representações zoomorfas: sua importância na cultura de Santarém - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2000)
The Tapajó - an indigenous group that inhabited the region of Santarém during the prehistoric period in Brazil - were undeniably a numerous and powerful group that through their archaeological remains and the historical accounts of travelers allows us to understand their social behavior. This work is a contribution to the technical-stylistic study of the zoomorphic representations present on ceramic fragments from the Frederico Barata Collection, held in MPEG's archaeological collection. Researchers from the Zoology Department were assisted in the identification of the animals, and a database was created to enable the digitization and relationship between the information found. With this, it is possible not only to have a better way of organizing these fragments within the collection, but also to have more precise information about the biological and physical characteristics of each animal represented. Divided into two stages, the work allows the opening of a discussion at the archaeological and anthropological level about the man-nature relationship present in Tapajó society. In this first phase, the fragments were quantified and classified using defined criteria that took into consideration the morphology, decoration and anatomical details of the animal representations.
The zoomorphic representations: their importance in the culture of Santarém
Keywords: Tapajó; Cerâmica; CNPQ::CIENCIAS HUMANAS::ANTROPOLOGIA